Patient Involvement Can Affect Clinicians' Perspectives and Practices of Infection Prevention and Control: A "Post-Qualitative" Study Using Video-Reflexive Ethnography. Issue 1 (24th January 2017) - Wyer, Mary; Iedema, Rick; Hor, Su-Yin; Jorm, Christine; Hooker, Claire; Gilbert, Gwendolyn L.
This study, set in a mixed, adult surgical ward of a metropolitan teaching hospital in Sydney, Australia, used a novel application of video-reflexive ethnography (VRE) to engage patients and clinicians in an exploration of the practical and relational complexities of patient involvement in infection prevention and control (IPC). This study included individual reflexive sessions with eight patients and six group reflexive sessions with 35 nurses. VRE usually involves participants reflecting on video footage of their own (and colleagues') practices in group reflexive sessions. We extended the method here by presenting, to nurses, video clips of their clinical interactions with patients, in conjunction with footage of the patients themselves analyzing the videos of their own care, for infection risks. We found that this novel approach affected the nurses' capacities to recognize, support, and enable patient involvement in IPC and to reflect on their own, sometimes inconsistent, IPC practices from patients' perspectives. As a "post-qualitative" approach, VRE prioritizes participants' roles, contributions, and learning. Invoking affect as an explanatory lens, we theorize that a "safe space" was created for participants in our study to reflect on and reshape their assumptions, positionings, and practices.